Estimation Risk of High Risk Building Project on Contractor - Imayanti Basari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The increasing need for space and limited land especially in big cities cause many high rise building projects in Indonesia. Construction projects including high rise building projects are located in complex and dynamic environments result in high levels of uncertainty and risk. Risks are always present in construction projects and often lead to delay schedules or cost overruns. Risk management is a process consisting of risk identification, qualitative and quantitative assessment, response with appropriate methods of handling and risk control. The concept of risk management is becoming very popular in a number of businesses. Many companies often create risk management procedures in their projects to improve performance, minimize losses and increase profits Risk event from a different project is different from the risk event on another project. Likewise, the level of occurrence and impact in each project is always changing from one project to another. This makes it difficult for management to handle risks on new projects. Lack of risk management, even inadequate risk analysis, can put construction projects in jeopardy. This research looked for alternatives to get risk event, concequance or impact estimates and likelihood or generic possibilities in order to be used to control the risk of subsequent high rise building projects. This research involves several high rise building projects that will be used as a basis for determining risk events, concequance or impact and likelihood or possibilities. In this study used qualitative methods, and data analysis is done by statistical analysis by finding the average of available data. Estimation this risk can help contractors, especially in the field of high rise building to manage risk both from risk factors, likelihood and consequence.